Formation of photoluminescents meso- and nanocrystals by hydrothermal microwave-assisted method - Eliziário, S. A. [UNESP]; Xavier, C. S. [UNESP]; Longo, E. [UNESP]; Varela, J. A. [UNESP] (My University, 2009)
In this letter, we report on the formation of mesostructures by the microwave-hydrothermal method. These materials were analyzed by X-ray diffraction (XRD), Field-emission gum scanning electron microscopy (FEG-SEM) and photoluminescence (PL) measurements. XRD patterns confirmed that these materials presented crystalline structures. FEG-SEM micrographs indicated that the meso- and nanostructures morphologies were formed due to an increase of effective collisions between the nanoparticles during the MH processing.